Data Mining Prediction of Oil Palm Fruit - Anisya (JAIA - Journal of Artificial Intelligence and Applications, 2021)
The development of information technology today is very meaningful for all circles. Currently, information technology has become a necessity in everyday life. The use of information technology is proven to facilitate human performance. Where the number of suppliers that supply palm oil fruit every year will affect the activities of companies engaged in palm oil production. So that currently the company needs a decision-making strategy in the procurement of oil palm fruit. Data mining is a technology that is very useful to help companies find very important information from data centers. Data mining predicts trends and characteristics of business behavior which are very useful to support important decision making. One of the techniques the writer uses is the Association Rule technique. Association Rule is a data mining technique to find association rules between item combinations. Using the Association Rule technique will help companies predict which suppliers will supply palm fruit in the following year. Meanwhile, to predict the load does not use the association rule method but uses existing data analysis.